Systems biology analyses reveal enhanced chronic morphine distortion of gut-brain interrelationships in simian human immunodeficiency virus infected rhesus macaques - Olwenyi, Omalla A.; Johnson, Samuel D.; Bidokhti, Mehdi; Thakur, Vandana; Pandey, Kabita; Thurman, Michellie; Acharya, Arpan; Uppada, Srijayaprakash; Callen, Shannon; Giavedoni, Luis; Ranga, Udaykumar; Buch, Shilpa J.; et al. (Frontiers in Neuroscience, 2022)
Background Commonly used opioids, such as morphine have been implicated in augmented SIV/HIV persistence within the Central Nervous System (CNS). However, the extent of myeloid cell polarization and viral persistence in different brain regions remains unclear. Additionally, the additive effects of morphine on SIV/HIV dysregulation of gut-brain crosstalk remain underexplored. Therefore, studies focused on understanding how drugs of abuse such as morphine affect immune dynamics, viral persistence and gut brain interrelationships are warranted. Methods For a total of 9 weeks, rhesus macaques were ramped-up, and a single daily injection of either morphine (n=4) or saline (n=4) administered. This was later followed with infection with SHIVAD8EO variants. At necropsy, mononuclear cells were isolated from diverse brain (frontal lobe, cerebellum, medulla, putamen, hippocampus (HIP) and subventricular zone (SVZ)) and gut (lamina propria (LP) and muscularis (MUSC) of ascending colon, duodenum, and ileum) regions. Multiparametric flow cytometry was used to were profile for myeloid cell polarity/ activation and results corroborated with indirect immunofluorescence assays. SHIV DNA levels were measured with aid of the digital droplet PCR assay. Luminex assays were then used to evaluate soluble plasma/ CSF biomarker levels. Finally, changes in the fecal microbiome were evaluated using 16s rRNA on the Illumina NovaSeq platform. Results Flow Cytometry-based semi-supervised analysis revealed that morphine exposure led to exacerbated M1(CD14/ CD16)/ M2 (CD163/ CD206) polarization in activated microglia that spanned across diverse brain regions. This was accompanied by elevated SHIV DNA within the sites of neurogenesis - hippocampus (HIP) and subventricular zone (SVZ). HIP/SVZ CD16+ activated microglia positively correlated with SHIV DNA levels in the brain (r = 0.548, p = 0.042). Simultaneously, morphine dependence depleted butyrate-producing bacteria, including Ruminococcus (p = 0.05), Lachnospira (p = 0.068) genera and Roseburia_sp._831b (p = 0.068). Finally, morphine also altered the regulation of CNS inflammation by reducing the levels of IL1 Receptor antagonist (IL1Ra). Conclusions These findings are suggestive that morphine promotes CNS inflammation by altering receptor modulation, increasing myeloid brain activation, distorting gut-brain crosstalk, and causing selective enhancement of SHIV persistence in sites of neurogenesis.